Revealing Elasmobranch Distributions in Turbid Coastal Waters: Insights From Environmental DNA and Particle Tracking - Nick Dunn; Sophie Ward; Joanna Barker; Jake Davies; Sarah Davies; Ben Wray; Peter Robins; Isabelle Apetroaie; Jake Williams; Kevin Hopkins; David Curnick (Ecology and Evolution)
ABSTRACT Many sharks, rays and skates are highly threatened and vulnerable to overexploitation, as such reliable monitoring of elasmobranchs is key to effective management and conservation. The mobile and elusive nature of these species makes monitoring challenging, particularly in temperate waters with low visibility. Environmental DNA (eDNA) methods present an opportunity to study these species in the absence of visual identification or invasive techniques. However, eDNA data alone can be difficult to interpret for species monitoring, particularly in a marine setting where its distribution can be influenced by water currents. In this study, we investigated the spatial and temporal distribution of elasmobranch species in two Special Areas for Conservation (SAC) off the coast of Wales. We took monthly eDNA samples for 1 year (starting September 2020 and March 2022 for the northern and southern SACs, respectively), and used metabarcoding to reveal the presence of elasmobranch species. We combined these data with hydrodynamic modelling and particle tracking methods to simulate the potential origins of the detected eDNA. We detected 11 elasmobranch species, including the critically endangered angelshark (Squatina squatina) and tope (Galeorhinus galeus). Most detections were in the spring and the fewest in the autumn. The particle tracking simulations predicted that eDNA was shed, on average, approximately 7 km and 15 km (in the northern and southern SACs, respectively) from the sampling stations at which it was detected. These results show that the two SACs represent important areas for elasmobranchs in the United Kingdom and demonstrate that eDNA methods combined with particle tracking simulations can represent a new frontier for monitoring marine species.